Local Coastal Water Masses Control Heat Levels in a West Greenland Tidewater Outlet Glacier Fjord. Issue 11 (9th November 2018) - Mortensen, J.; Rysgaard, S.; Arendt, K. E.; Juul‐Pedersen, T.; Søgaard, D. H.; Bendtsen, J.; Meire, L.
Abstract: Fjords form the gateway between the open ocean and the Greenland Ice Sheet (GIS) and consequently play a crucial role for the stability of the Ice Sheet. Hydrographic observations, especially with seasonal resolution, from these fjords are limited making it difficult to assess linkages between the fjord, coastal water masses, and freshwater discharge from GIS. Here we present a decade‐long monthly hydrographic time series from a southwest Greenland fjord in direct contact with GIS. Our observations reveal significant temporal and spatial water mass variations related to coastal, glacial, and atmospheric dynamics. During winter, the fjord circulation is dominated by seasonal dense coastal inflows and the timing of these inflows determines intermediate and deepwater temperatures. During summer, runoff from GIS leads to a pronounced freshening of the fjord. In general, the fjord's seasonal circulation system damps the seasonal variation in temperature in the fjord. This leads to a seasonal temperature range in the intermediate layer in the inner part of the fjord that is half the observed range at the fjord entrance. Changes in mean water temperatures in the intermediate layer seem predominantly linked to local coastal water masses, where cold winter/warm summer events decrease/increase the mean water temperatures. Consequently, these events play an important role in heat transport toward glacier termini. Key Points: We present a decade‐long seasonal hydrographic time series from a major Greenland tidewater outlet glacial fjord The fjord's seasonal circulation system damps the coastal temperature signal in the fjord Mean temperature shifts in the inner fjord are predominantly linked to local coastal water masses and can be related to local atmospheric forcing